Scenarios of the Imaginary : Theorizing the French Enlightenment - Harari, Josue V. (Cornell University Press, 2019)
From Proust to Beckett, from Blanchot to Derrida from Freud to Lacan, and from Lévi-Strauss to René Girard, all of our theories of modernity have been predicated upon a nostalgia for the real. In this lively and perceptive diagnosis of the malaise of contemporary theorists, Josué Harari interprets the French Enlightenment in terms of the relationship between theory and the imaginary, and explores the paradox by which theories that purport to describe the real lack any dimension of reality. Through readings of texts by some of the progenitors of influential modem theories, Harari explores the working strategies of the imaginary. In particular, he illuminates the founding moment, an instant of personal crisis for the author, during which a theory is infused by a fictional scenario: Montesquieu's "phantasm" of the body, resulting in his theory of government; Rousseau's narcissistic delirium in Emile, resulting in his theory of education; the theory of psychoanalysis, resulting from Freud's unconscious motives for choosing the Oedipal theory over the seduction theory of neurosis; and the theory of structural anthropology, generated by a psychodrama in Tristes Tropiques which Harari reads as a symptom of Lévi-Strauss's anguish when he is confronted with reality. Two striking chapters on Sade at the center of the book reveal the operation of the theoretical imaginary in libertine discourse. Scenarios of the Imaginary will find a wide audience among students and scholars of French literature, particularly of the eighteenth century, and of contemporary French thought, and among comparativists, literary theorists, anthropologists, and historians.